Functional Characterization of Brain Tumor-Initiating Cells: Implications for Preclinical Models and Drug Development. (1st September 2019) - Garcia, Cesar A; Bhargav, Adip Guruprasad; Mondal, Sujan K; ReFaey, Karim; Zarco, Natanael; Schiapparelli, Paula; Sarabia-Estrada, Rachel; Guerrero-Cazares, Hugo; Quiñones-Hinojosa, Alfredo
Abstract: INTRODUCTION: Glioblastoma (GBM) is the deadliest and most common primary brain cancer in adults. Brain tumor-initiating cells (BTICs) are a heterogeneous subset of stem-like, invasive cells that play a critical role in treatment failure and recurrence. METHODS: Here, we propose a system to functionally characterize patient-derived BTICs to identify features that will guide assessment of therapeutics in a BTIC subpopulation-specific manner. We established and evaluated 5 BTIC populations based on (1) proliferation, (2) stemness, (3) migration, (4) tumorigenesis, (5) clinical characteristics, and (6) therapeutic sensitivity. RESULTS: Overall, in Vitro growth trends reflected in Vivo growth rates. However, a significant difference was found between tumor growth in male versus female mice in 3 BTIC lines (QNS108 P  = .0011; QNS120 P  < .0001; QNS 140 P  < .0001). Differences in survival were observed, where BTICs derived from male and female patients produced faster morbidity in mice of the opposite sex (male derived QNS108 male vs female P  = .0039; female derived QNS203 male vs female P  = .029). QNS203, which was isolated from a tumor in contact with the anterior subventricular zone, decreased survival at a faster rate compared to other cell lines (n = 10 per line, 5 males/5 females, P  < .0001). Stem-like properties of BTICs were assessed via differentiation marker expression, sphere-forming capacity, and detection of canonical marker CD133. Higher CD133 expression correlated with faster in Vitro doubling time and greater tumor burden. Histology reflected similar patient tumor features such as migration across the corpus callosum and cystic formation. BTICs revealed varying responses to therapies (TMZ, Radiation, TRAIL, BMP4) and varied competence to retroviral transduction. CONCLUSION: By studying the functional features of BTICs within our model of GBM heterogeneity, it was shown that several factors influenced tumorigenesis and survival. These included original tumor location, stemness, variation in therapeutic sensitivity, and a critical finding for the role of sex, an unexplored area for creating next-generation, sex-specific, and BTIC-specific therapeutics.